Could Al-Qaida turn African in the Sahel? - (:unkn) unknown (My University, 2010)
Lightly patrolled borders, sparsely populated areas, and recent terrorist activity raise fears that the Sahel is a fertile ground for jihadist movements, notably al-Qaeda in the Islamic Maghreb (AQIM). Regional cooperation and discreet aid from the West are critical for countries to regain control of their territory and prevent al-Qaeda from gaining ground in Africa, asserts a paper by Jean-Pierre Filiu.
Keywords: African Research